Proof of concept study of the posterior quadratus lumborum block for laparoscopic myomectomy: A randomized controlled trial - Christopher Little; Natale Naim; Tristan Grogan; Steve Yu; Pamela A. Chia (PLoS ONE, 2025)
In the United States, 65,000 myomectomies are performed annually to treat uterine fibroids. The quadratus lumborum block (QLB) is an effective block for laparoscopic pelvic surgery, urologic surgery, hip surgery and cesarean sections, with limited data for laparoscopic myomectomies. We evaluated the posterior QLB in reducing MME consumption and numeric rating scale (NRS) pain scores in patients undergoing laparoscopic myomectomies. Twenty-two subjects were enrolled in this single-center, randomized, controlled study between March 28, 2019 and June 16, 2020 and were randomized to either the QLB or control group. Seven subjects were excluded from the final analysis, 5 after being lost to follow-op and 2 for not meeting the inclusion criteria. Recipients in the QLB group received bilateral posterior QLBs, with 30 mL of 0.25% ropivacaine per injection. The primary outcome of MME use at 24 hours was not significant between the QLB group and the control group (23.3 ± 8.5 mg vs. 25.7 ± 14.4 mg, p = 0.859). The secondary outcome of NRS pain scores was also not significant between groups (p > 0.05). While this study did not provide evidence that QLB may be useful in reducing opioid consumption or pain scores in patients undergoing laparoscopic myomectomies, further studies with a larger sample size will be valuable to determine the effectiveness of this block for laparoscopic myomectomy.